Theoretical investigations of electronic spectra of silver atom using all-electron scalar relativistic basis - Chaudhuri, Rajat K.; Chattopadhyay, Sudip (AIP advances, 2022)
Exploration of the tractable size basis set that can provide reliable estimates of computed properties for systems containing heavy elements has been the subject of interest in quantum chemistry over many decades. In this connection, the recently developed segmented all-electron relativistically contracted (SARC) basis set proposed by Rolfes et al. [J. Comput. Chem. 41, 1842 (2020)] appears to be worth studying. In the present attempt, ground and excited state properties of the Ag atom is computed on this basis at the Fock-space multi-reference coupled cluster (FSMRCC) level of theory with four-component relativistic spinors. The computed quantities resulting from the SARC basis are subsequently compared with those obtained using an even-tempered basis to assess the efficacy of the SARC basis. Computations have also been performed with the extended SARC basis to improve the quality of the property of interest. The accuracy of the computed quantities such ionization energy, electron affinity, excitation energies, etc., obtained using the SARC basis at the FSMRCC level of theory demonstrates that the SARC basis (particularly the extended one), which is primarily designed for quantum chemical calculations at the two-component scalar relativistic level for systems containing heavy atoms, can be used for fully relativistic calculations. The magnetic dipole hyperfine structure constant A, oscillator strengths f and transition rates Afi calculated using the SARC basis also agree well with the experiment and with the available theoretical estimates.